Assessing the impact of climate change on the net ecosystem exchange of Irish grasslands : a case study of CO₂ efflux using multiple microcosm enclosure facilities - Fitton, Nuala (Trinity College (Dublin, Ireland). Department of Botany, 2013)
It is now widely accepted that human activity is having a discernible effect on the global climate, and these changes will impact upon the functioning of many of the planet's natural systems (Cox et al, 2000; Trumbore, 2006). Grassland ecosystems exhibit a large interannual variability in their annual NEE (Flanagan et al., 2002, Ma et al., 2007) and as a consequence their role in the global C cycle remains uncertain.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin.